Onset of differentiation is post-transcriptionally controlled in adult neural stem cells - Baser, Avni; Kleber, Susanne; Schefzik, Roman; Schultz, Carsten; Fischer, Bernd; Martín-Villalba, Ana (Nature, 2019)
Whether post-transcriptional regulation of gene expression controls differentiation of stem cells for tissue renewal remains unknown. Quiescent stem cells exhibit a low level of protein synthesis1, which is key to maintaining the pool of fully functional stem cells, not only in the brain but also in the bone marrow and hair follicles2,3,4,5,6. Neurons also maintain a subset of messenger RNAs in a translationally silent state, which react ‘on demand’ to intracellular and extracellular signals. This uncoupling of general availability of mRNA from translation into protein facilitates immediate responses to environmental changes and avoids excess production of proteins, which is the most energy-consuming process within the cell. However, when post-transcriptional regulation is acquired and how protein synthesis changes along the different steps of maturation are not known. Here we show that protein synthesis undergoes highly dynamic changes when stem cells differentiate to neurons in vivo. Examination of individual transcripts using RiboTag mouse models reveals that whereas stem cells translate abundant transcripts with little discrimination, translation becomes increasingly regulated with the onset of differentiation. The generation of neurogenic progeny involves translational repression of a subset of mRNAs, including mRNAs that encode the stem cell identity factors SOX2 and PAX6, and components of the translation machinery, which are enriched in a pyrimidine-rich motif. The decrease of mTORC1 activity as stem cells exit the cell cycle selectively blocks translation of these transcripts. Our results reveal a control mechanism by which the cell cycle is coupled to post-transcriptional repression of key stem cell identity factors, thereby promoting exit from stemness.